Peran Kepemimpinan Kepala Sekolah, Kemampuan Guru, dan Atmosfer Sekolah dalam Mempengaruhi Kinerja Guru SD di Distrik Mulia, Puncak Jaya - Barton Wenda; Marthinus Kayame; Amos Rombe (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2026)
This purposes of this study is to examine and assess, through empirical evidence, how principal leadership has an impact on teachers’ performance, considering the separate and combined effects of the relevant variables. A quantitative method was utilized, applying an explanatory research framework. The research employed a total sampling method, engaging 72 respondents, with every teacher participating as research subjects. Data gathering was carried out via observation, analysis of documents, and the distribution of questionnaires. The data was then processed with SPSS version 19 and analyzed using both simple and multiple linear regression models. T-tests were utilized for hypothesis testing to assess partial effects, while F-tests were employed to analyze simultaneous effects. The results show that principal leadership explains 17% of the variance in teaching performance. Meanwhile, educator competence contributes 5%, and school climate accounts for 10.4%. When examined jointly, the collaboration of principal leadership and educator competence shows 18.6% of the variance in teaching performance. In addition, the interaction between principal leadership and school climate contributes 20.9%. Furthermore, the combined effect of teacher competence and school climate accounts for 7.8%. Overall, principal leadership, teacher competence, and school climate collectively explain 23.5% of the variation in educator performance.